Banking and financial systems - Sarma, V. Nityananda (New Delhi, 2011)
Banks are the most significant players in the Indian financial market. The Indian banking system has played a crucial role in the socioeconomic development of the country. After 1990, the Government of India formulated policies supporting liberalisation, privatisation and globalisation. The book keeps pace with these changes and captures the central themes and concerns of corporate financial management. The topics covered in the book are discussed in a fairly self-contained manner. It addresses contemporary financial components such as capital market, money market, banker and customer relationship, cooperative banks, regional rural banks, RBI, SBI, development banking and banking technology. Besides, it explains the assessment of working capital, the appraisal of term loans from a practitioner's point of view, and also provides an overview of the financial market, security analysis and portfolio management.
Keywords: Banks and banking